2005
DOI: 10.1007/s11181-006-0036-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging and plastic deformation on the mechanical, magnetic, and thermal properties of cobalt-containing invars

Abstract: The mechanical, magnetic, and thermal properties of water-quenched (from 1150 ° C) alloys, such as ç 36 ä 10 í 3, ç 36 ä 10 ï5í 2, and ç 36 ä 5 í 2, which were strengthened by aging (at 650 ° C) and high-temperature deformation (1100-800 ° C) followed by aging, are studied. The decomposition of a supersaturated solid solution in the Invar alloys under study was shown to increase the strength properties and coercive force but to decrease the plasticity and saturation magnetization. In this case, the aging ambig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Fe-36Ni [5,11], Fe-Ni-Co [12,17,18], Fe-Ni-Ti [19] and Fe-Ni-Mo [10,16], etc. Vinogradov et al [5] reported that the tensile strength of the base Fe-36Ni alloy can be increased up to 912 MPa when its mean grain size was refined to 0.18 μm by the equal-channel angular pressing (ECAP).…”
Section: Introductionmentioning
confidence: 99%
“…Fe-36Ni [5,11], Fe-Ni-Co [12,17,18], Fe-Ni-Ti [19] and Fe-Ni-Mo [10,16], etc. Vinogradov et al [5] reported that the tensile strength of the base Fe-36Ni alloy can be increased up to 912 MPa when its mean grain size was refined to 0.18 μm by the equal-channel angular pressing (ECAP).…”
Section: Introductionmentioning
confidence: 99%
“…Fe-Ni binary alloy with a Ni content of ~36 wt.% is known as invar alloy, which shows a very low coefficient of thermal expansion (CTE) of almost zero under 100 °C [1,2,3,4]. Such an anomalous thermal expansion effect of the Fe-36Ni alloy is known as the invar effect [5].…”
Section: Introductionmentioning
confidence: 99%